Compliance With Contribution Payments For Independent National Health Insurance Contributors-Related Factors - Noerjoedianto, Dwi; Putri, Mustika; Solida, Adila (Chakra Brahmanda Lentera Institute, 2023)
Background: National Health Insurance (JKN) is a government program designed to meet the health care needs of the Indonesian population. The amount of delinquent BPJS contributions is due to JKN Mandiri participants' failure to pay contributions. This study aims to determine factors associated with independent JKN participants' payment of dues at Abdul Manap Hospital in Jambi City. Methods: This study employs a quantitative approach and a cross-sectional design. The sample consisted of 106 random samples collected using the technique of accidental sampling. In this study, the independent variables are education, occupation, income, knowledge, perception, and payment location, while the dependent variable is JKN contribution payment compliance. Respondents filled out questionnaires to generate data. The data analysis consisted of univariate and bivariate (chi-square) tests. Results: The majority of respondents, or 63.2%, do not comply with paying JKN contributions, according to the findings of this study. This study's statistical analyses indicate that education (0.007), occupation (0.008), income (0.000), knowledge (0.016), perception (0.008), and place of payment are associated with JKN contribution compliance (0.001). Conclusion: There is a correlation between education, occupation, income, knowledge, perception, payment location, and JKN contribution payment compliance.